2023
DOI: 10.1097/prs.0000000000010465
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a xenograft model with CD-1 nude mice to study human skin wound repair

Abstract: Background: A significant gap exists in the translatability of small-animal models to human subjects. One important factor is poor laboratory models involving human tissue. Thus, the authors have created a viable postnatal human skin xenograft model using athymic mice. Methods: Discarded human foreskins were collected following circumcision. All subcutaneous tissue was removed from these samples sterilely. Host CD-1 nude mice were then anesthetized, and dorsal skin was sterilized. A 1.2-cm-diameter, full-thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…(14,32) This tool allows for unbiased, quantitative assessment of the complex architecture of fibrotic tissue, and allows for specimens to be objectively compared on the basis of their ECM ultrastructure. We have previously validated this image analysis pipeline in multiple fibrotic conditions across species (including mouse, pig, and human) (14,(32)(33)(34)(35)(36) and have shown that the fibrotic ECM features measured by our algorithm are clinically relevant (strongly predictive of highly clinically significant differences in patient survival in pancreatic cancer (32)).…”
Section: Tension Offloading Prevents and Mitigates Fibrotic Shifts In...mentioning
confidence: 99%
See 1 more Smart Citation
“…(14,32) This tool allows for unbiased, quantitative assessment of the complex architecture of fibrotic tissue, and allows for specimens to be objectively compared on the basis of their ECM ultrastructure. We have previously validated this image analysis pipeline in multiple fibrotic conditions across species (including mouse, pig, and human) (14,(32)(33)(34)(35)(36) and have shown that the fibrotic ECM features measured by our algorithm are clinically relevant (strongly predictive of highly clinically significant differences in patient survival in pancreatic cancer (32)).…”
Section: Tension Offloading Prevents and Mitigates Fibrotic Shifts In...mentioning
confidence: 99%
“…To address this question, we employed a human foreskin xenograft model, which we have previously validated and used to study the effects of potential anti-fibrotic interventions. (36,40) We engrafted human foreskin samples onto the dorsum of immune-deficient mice (CD-1 nude -to prevent graft rejection), as previously reported, (36) then subjected xenografts to repeated injections of bleomycin with or without adjunct injections of recombinant IL4 protein; other grafts were made and not injected with bleomycin, as an UW/non-fibrotic control (Fig. 4A-B).…”
Section: Recombinant Il4 Reduces Bleomycin-induced Fibrosis In a Huma...mentioning
confidence: 99%